Kebijakan Luar Negeri Amerika Serikat Terhadap Iran Selama Pandemi Covid-19 - Assri, Bahy Chemy Ayatuddin (Jurnal ICMES, 2020)
This paper aims to analyze the United States' (US) foreign policy towards Iran during the Covid-19 pandemic. Before the pandemic era, the US had imposed sanctions on Iran, including an oil export embargo. The Covid-19 pandemic made Iran increasingly squeezed by the economic burden and again demanded the US to stop its embargo. However, the US did not revoke sanctions and even tightened the sanctions by putting several companies on the blacklist for business with Iran. The analysis in this article uses the realism approach, which considers that the actions of each country are always related to the aspects of survival and self-help that give rise to the security dilemma. This research is qualitative, and the data used are secondary in the form of documents and mass media articles. This article finds that the extension of the US’ embargo on Iran is a form of US survival in order to prevent the emergence of new nuclear power in the region, which is seen as a threat to the US.